TEKST KOMPONENTLERIN BAYLANÍSTÍRÍWShÍ QURALLAR - Dosjanova, G. (SCIENCE and SOCIETY, 2024)
The article is about the means of linking components of the text. Here the role of various forms of the predicate, pronouns, lexical repetitions, chiasmatic constructions synonyms, conjunctions and introductory clauses in linking the components of the text is given by analysing examples from literary work.